Awareness of preconception care among women and men: A study from Jordan. (April 2015) - Al-Akour, N. A.; Sou'Ub, R.; Mohammad, K.; Zayed, F.
Abstract The objective of this study was to examine awareness of Jordanian married women and men of preconception care. A total of 763 (537 women and 226 men) Jordanians who attended maternal and child healthcare centres in a city, in the centre of Jordan, were included in the current study. The Health before Pregnancy Questionnaire was used to collect the data from participants, while they waited to be seen by the healthcare provider in the health centres. Family history of chronic disorders, 1st-degree consanguineous marriages and planning pregnancy were associated with awareness of preconception care. Around 50% of participants were aware of the serious impact that a woman's and man's family history can have on the health of their babies. The majority of participants were aware of changes that should be made prior to conception.